Quantifying national abundance changes of raptors across Botswana using repeat road surveys - Mphetlhe, Rochelle (Department of Biological Sciences, 2024)
Raptors are a group of carnivorous birds experiencing considerable population declines across the globe. Despite these declines, many raptor populations remain poorly monitored across most of their ranges and, as with most biodiversity, this is especially true in developing countries, including most countries within Africa. In Botswana, conservationists are growing increasingly concerned about the population trends of many raptor species, especially vultures. Fortuitously, Botswana has over 55,000 km of raptor road transectsurveys originally conducted between 1991-1995. Over two decades later, researchers repeated some of those surveys (c. 21,000 km) in the northern part of Botswana, which revealed declines across multiple raptor species. To complete these re-surveys at a national level, we undertook a repeat of the raptor transect surveys conducted in the southern half of Botswana, covering c. 22,000 km of transects. We then estimated country-wide abundance changes for all species of regularly occurring raptors by combining these two re-surveys. We explored changes for 30 species, 19 (63%) of which exhibited significant changes. Fifteen species (50%) declined significantly, and 4 (13%) species increased significantly, while 11 species (37%) showed nonsignificant declines. Most species displayed similar population trends between the national analysis and the northern re-surveys. Those re-surveys revealed significant declines in 48% of the 29 species examined. The Lappet-faced Vulture (Torgos tracheliotus) showed significant declines of 61% in the northern re-surveys, but in the national analysis, revealed nonsignificant increases of 27%. White-backed Vultures (Gyps africanus) also revealed significant increases of 28% in the national analysis compared to declines shown in the northern resurveys. Whilst our re-surveys suggestsimilarly worrying trends of many raptor species as the northern re-surveys did, we noted increasing population abundance trends for three of the most threatened vulture species. Future research should explore whether certain environmental data (e.g., human modification, climate change, etc.) are associated with the declines of these species, to better understand the drivers for these declines